Pedagogical Approach to Developing Linguistic Competence through Contextual Semantics in Classical Texts - Syuhadak; Inayatur Rosyidah; Muh Zamroni; Usfiyatur Rusuly; Yesi Darasita; Faisal Mahmoud Adam Ibrahim (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study aimed to examine the effectiveness of contextual semantic theory in the teaching of Qirā’ah al-Kutub as a means to strengthen students’ linguistic competence. The approach emphasizes understanding word meanings (mufradāt) within social, cultural, and pragmatic contexts rather than focusing solely on grammatical structures. A descriptive-qualitative method was used, with data collected through questionnaires and interviews involving 10 students from the Islamic Family Law program who studied classical texts from Fiqh al-Sunnah. The findings indicated a significant improvement in meaning comprehension, learning motivation, and students' interpretative skills. Contextual semantics proved relevant for Arabic language education, especially in enhancing the ability to read and understand authentic texts. This research contributes to the development of context-based linguistic pedagogy in advanced Arabic language learning.